Analysis Of Success Factors For The Social Innovation Program For Unlivable Houses In Central Java Province - Pratisto Nugroho; Hardi Nugroho; Sri Puryono; Kismartini Kismartini (LPPM Universitas PGRI Sumatera Barat, 2024)
Community welfare can be measured from the fulfillment of basic human needs. A healthy place to live and living environment is one of the basic needs that must be met. People's personalities can be formed and influenced by the conditions in which they live and their environment. This research aims to analyze and identify factors that support and hinder Social Innovation in managing the Social Rehabilitation Program for Uninhabitable Houses in Central Java . The main data analysis technique used is qualitative data analysis. Research on social innovation in alleviating poverty in Central Java Province through the RTLH Hospital assistance program which was carried out by researchers some time ago, the results of which are the supporting factors in researching social innovation in alleviating poverty through the RTLH Hospital assistance program in Central Java Province, namely individual factors and system. Meanwhile, the inhibiting factors in researching social innovation in alleviating poverty through the RTLH Hospital assistance program in Central Java Province are organizational and network factors. The organizational factor is an obstacle in this research, because there is no integrated and sustainable social work process from all community organizations in the current development of improvements to the RTLH Hospital in Central Java Province. And the network factor is another inhibiting factor in this research, because up to now the people receiving RTLH Hospital assistance have not received training programs, education or courses to increase their income. So the use of new, more modern technology to improve the welfare of their families cannot be realized in real terms by the Central Java Provincial Government at this time.